The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1016/j.bjorl.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Cancer treatment in determination of hearing loss

Abstract: Cancer treatment causes hearing loss, associated with the administration of chemotherapy and radiotherapy. Cyclophosphamide increased the risk of causing hearing loss. Complaints of tinnitus and speech understanding difficulty were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
(25 reference statements)
1
5
0
1
Order By: Relevance
“…Concerning the radiotherapy treatment, our findings showed a significant association with the occurrence of tinnitus, corroborating with Oliveira et al (2016), who also found toxic effects on the hearing of women who received the same treatment for ovarian, cervical, and uterine cancer 23 . Breast cancer treatment showed tinnitus (49.2%) as the main symptom of sequelae of the auditory system, with few occurrences of hearing loss (7.7%).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Concerning the radiotherapy treatment, our findings showed a significant association with the occurrence of tinnitus, corroborating with Oliveira et al (2016), who also found toxic effects on the hearing of women who received the same treatment for ovarian, cervical, and uterine cancer 23 . Breast cancer treatment showed tinnitus (49.2%) as the main symptom of sequelae of the auditory system, with few occurrences of hearing loss (7.7%).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding radiotherapy, although most studies indicate a strong relationship of ototoxicity to head and neck tumors [32][33][34] , simultaneous administration to chemotherapeutic agents can potentiate the effects of cell apoptosis in the cochlea 35 . Previous investigations that have verified the effect of treatment with chemotherapy and radiotherapy on breast, cervical and uterine neoplasms in the auditory system report the presence of hearing loss in both treatments 23 . Therefore, this study analyzed the occurrence of tinnitus and peripheral sensory neuropathy in women during chemotherapy for breast cancer.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…O aumento da ocorrência de câncer é decorrente do envelhecimento da população e da elevada prevalência dos fatores de risco, ou seja, devido ao estilo de vida contemporâneo que pode favorecer a formação de tumores (Torre et al, 2012). O tratamento do câncer pode ser realizado por meio de cirurgia, quimioterapia, hormonioterapia e, em alguns casos, transplante de medula óssea Santos et al (2011) ou ainda pela utilização de diferentes classes de medicamentos, como aminoglicosídeos, agentes antineoplásicos, antibióticos, anti-inflamatórios não esteroidais, diuréticos, entre outros (Oliveira et al, 2016).…”
Section: Introductionunclassified
“…Different classes of medications are used in the treatment of cancer, such as aminoglycosides, anti-tumor agents, antibiotics, non-steroidal anti-inflammatory drugs, diuretics and anti-hypertensive agents, some of which are considered ototoxic (3) . Medications derived from platinum are the most devastating and have the following side effects when used at cumulative doses higher than 360 mg/m 2 : nausea, vomiting, nephrotoxicity, myeolsuppression and ototoxicity (4) .…”
Section: Introductionmentioning
confidence: 99%